Introduction of H2-Uptake Hydrogenase Genes Into Rhizobial Strains Improves Symbiotic Nitrogen Fixation in Vicia sativa and Lotus corniculatus Forage Legumes - Sotelo, Mariana; Ureta, Ana Claudia; Muñoz, Socorro; Sanjuán, Juan; Monza, Jorge; Palacios, Jose (Frontiers in Agronomy, 2021)
Biological nitrogen fixation by the Rhizobium-legume symbiosis allows the conversion of atmospheric nitrogen into ammonia within root nodules mediated by the nitrogenase enzyme. Nitrogenase activity results in the evolution of hydrogen as a result of a side reaction intrinsic to the activity of this enzyme. Some rhizobia, and also other nitrogen fixers, induce a NiFe uptake hydrogenase (Hup) to recycle hydrogen produced by nitrogenase, thus improving the efficiency of the nitrogen fixation process. In this work we report the generation and symbiotic behavior of hydrogenase-positive Rhizobium leguminosarum and Mesorhizobium loti strains effective in vetch (Vicia sativa) and birsfoot trefoil (Lotus corniculatus) forage crops, respectively. The ability of hydrogen recycling was transferred to these strains through the incorporation of hup minitransposon TnHB100, thus leading to full recycling of hydrogen in nodules. Inoculation of Vicia and Lotus plants with these engineered strains led to significant increases in the levels of nitrogen incorporated into the host legumes. The level of improvement of symbiotic performance was dependent on the recipient strain and also on the legume host. These results indicate that hydrogen recycling has the potential to improve symbiotic nitrogen fixation in forage plants.